2018
DOI: 10.1111/acer.13863
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Epigenetic Alterations Caused by Alcohol: A Promising Therapeutic Direction for Alcoholic Liver Disease

Abstract: Alcoholic liver disease (ALD), a liver function disorder caused by excessive alcohol intake, is a serious threat to global public health and social development. Toxic metabolites and reactive oxygen species produced during the metabolism of alcohol can alter the epigenetic state including DNA methylation, histone modifications, and expression of microRNAs. Epigenetic alterations can conversely involve various signaling pathways, which could contribute to the initiation and progression of ALD. To elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…It has been reported that chromatin remodeling is involved in COX-2-induced cellular events, as evidenced by a recent study that demonstrates the DNA methylation of specific oncogenes in COX-2-overexpressing mice ( Chen et al, 2017 ). While recent studies suggesting that histone and mitochondrial protein acetylation in a high fat diet evoke protein hyper-acetylation are controversial ( Carrer et al, 2017 ; Choi & Friso, 2010 ; Meyer et al, 2018 ; Peterson et al, 2018 ), the contribution to the hyper-acetylation status from the ethanol diet is more widely accepted ( Choi & Friso, 2010 ; Jung & Metzger, 2015 ; Kriss et al, 2018 ; Lin et al, 2018 ; Zhong et al, 2010 ; Zhong & Lemasters, 2018 ). A recent approach using 13 C-labeled ethanol together with mass spectrometry in an ethanol binge drinking mouse model provided the quantitative evidence of histone hyper-acetylation status ( Kriss et al, 2018 ), and we would like to employ this method in our future studies to significantly improve our understanding of the critical steps in nutritional rerouting in dietary stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chromatin remodeling is involved in COX-2-induced cellular events, as evidenced by a recent study that demonstrates the DNA methylation of specific oncogenes in COX-2-overexpressing mice ( Chen et al, 2017 ). While recent studies suggesting that histone and mitochondrial protein acetylation in a high fat diet evoke protein hyper-acetylation are controversial ( Carrer et al, 2017 ; Choi & Friso, 2010 ; Meyer et al, 2018 ; Peterson et al, 2018 ), the contribution to the hyper-acetylation status from the ethanol diet is more widely accepted ( Choi & Friso, 2010 ; Jung & Metzger, 2015 ; Kriss et al, 2018 ; Lin et al, 2018 ; Zhong et al, 2010 ; Zhong & Lemasters, 2018 ). A recent approach using 13 C-labeled ethanol together with mass spectrometry in an ethanol binge drinking mouse model provided the quantitative evidence of histone hyper-acetylation status ( Kriss et al, 2018 ), and we would like to employ this method in our future studies to significantly improve our understanding of the critical steps in nutritional rerouting in dietary stress.…”
Section: Discussionmentioning
confidence: 99%
“…The role of microRNA (miRNA) in the pathogenesis of ARLD has been reviewed extensively over the years. [14,35,[160][161][162][163][164]. Dysregulation of miRNAs in ARLD is linked to the development of steatosis (yellow circle), inflammation via recruitment of inflammatory cells (blue circle), fibrosis (blue lines) and HCC (green circle).…”
Section: Figure Legendmentioning
confidence: 99%
“…In addition to the deacetylation function, SIRT1 promotes the conversion of the metabolite of ethanol acetic acid into acetyl-CoA, which acetylates histones under the catalysis of HATs (Sahar et al, 2014;Lin et al, 2018). Therefore, SIRT1 may be involved in the balance of gene silencing and activation in ALD via acetylation of histones.…”
Section: Histone Acetylation In Aldmentioning
confidence: 99%
“…However, acetaldehyde is rapidly oxidized to acetate under the catalysis of aldehyde dehydrogenase 2 (ALDH2) inside mitochondria, accompanied with NAD+ consumption and NADH production ( Osna et al, 2017 ). The pathogenesis of ALD is quite complex and results from the interaction of multiple mechanisms ( Lin et al, 2018 ; Sehrawat et al, 2020 ). The metabolism of ethanol in the liver produces abundant reactive oxygen species (ROS) and alters the balance between lipogenesis and fatty acid metabolism, leading to hepatic steatosis ( Xu et al, 2017 ).…”
Section: Histone Modifications In Cldsmentioning
confidence: 99%
See 1 more Smart Citation